Slow‐to‐Fast Deformation in Mafic Fault Rocks on an Active Low‐Angle Normal Fault, Woodlark Rift, SE Papua New Guinea. (1st November 2020) - Mizera, M.; Little, T.; Boulton, C.; Prior, D.; Watson, E.; Biemiller, J.; White, J.; Shigematsu, Norio
Abstract: Slip on the active Mai'iu low‐angle normal fault in Papua New Guinea that dips 15–24° at the surface has exhumed in its footwall a single, continuous fault surface across a >25‐km‐wide dome. Derived from a metabasaltic protolith, the fault zone consists of a <3‐m‐thick zone of gouges and cataclasites that overprint a structurally underlying carapace of extensional mylonites. Detailed microstructural and geochemical data, combined with chlorite‐based geothermometry, reveal changing deformation processes and conditions in the Mai'iu fault rocks as they were exhumed. The microstructure of nonplastically deformed actinolite grains inherited from the fine‐grained (6–35 µm) metabasaltic protolith indicates that shearing at depth was controlled by diffusion creep accompanied by grain‐boundary sliding of these grains together with chlorite neo‐crystallization at T > 275°C–370°C. In a foliated cataclasite unit at shallower crustal levels (T ≈ 150°C–275°C), metasomatic reactions accompanied fluid‐assisted mass transfer processes that accommodated aseismic, distributed shearing; pseudotachylites and ultracataclasites in the same unit indicate that such creep was punctuated by episodes of seismic slip—after which creep resumed. At the shallowest levels (T < 150°C), gouges contain abundant saponite, a frictionally weak mineral that promotes creep on the shallowest dipping (≤24°), most poorly oriented part of the Mai'iu fault. Our field, microstructural and geochemical data of freshly exhumed fault rocks support geodetic, seismological, and geomorphic evidence for mixed seismic‐to‐aseismic slip on this active low‐angle normal fault. Key Points: Fault rock microstructures reveal slow‐to‐fast slip on an active detachment fault that dips 15–24° at the Earth's surface Pseudotachylites, foliated cataclasites, and ultracataclasites developed in a zone of mixed mode, seismic‐to‐aseismic slip behavior Frictionally weak saponite in fault gouge promotes slip on the most poorly oriented, surficial part (<24°) of the Mai'iu fault